2018
DOI: 10.1038/s41598-018-21355-4
|View full text |Cite
|
Sign up to set email alerts
|

Introgression of a functional epigenetic OsSPL14WFP allele into elite indica rice genomes greatly improved panicle traits and grain yield

Abstract: Rice yield potential has been stagnant since the Green Revolution in the late 1960s, especially in tropical rice cultivars. We evaluated the effect of two major genes that regulate grain number, Gn1a/OsCKX2 and IPA1/WFP/OsSPL14, in elite indica cultivar backgrounds. The yield-positive Gn1a-type 3 and OsSPL14WFP alleles were introgressed respectively through marker-assisted selection (MAS). The grain numbers per panicle (GNPP) were compared between the recipient allele and the donor allele groups using segregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 40 publications
3
33
1
Order By: Relevance
“…When we compared the conserved domains of TaSBP protein sequences with DNAman 6.0, we found that a few sites in the SBP domain coding region had an amino acid substitution ( Figure 13). For example, in the first zinc-binding site, Cys(8)-Cys(25)-His(28)-Cys (30), His was replaced by Cys in TaSBP1-ALa, TaSBP1-BLa, TaSBP1-BLb, and TaSBP1-Dla. The other zinc-binding site in wheat SBPs is Cys(45)-Cys(48)-Cys(63)-His (70).…”
Section: Protein Features and Conservative Domain Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…When we compared the conserved domains of TaSBP protein sequences with DNAman 6.0, we found that a few sites in the SBP domain coding region had an amino acid substitution ( Figure 13). For example, in the first zinc-binding site, Cys(8)-Cys(25)-His(28)-Cys (30), His was replaced by Cys in TaSBP1-ALa, TaSBP1-BLa, TaSBP1-BLb, and TaSBP1-Dla. The other zinc-binding site in wheat SBPs is Cys(45)-Cys(48)-Cys(63)-His (70).…”
Section: Protein Features and Conservative Domain Analysesmentioning
confidence: 99%
“…Recently, Ma et al showed that CmSBP11 was involved in the metabolism of vitamin C during muskmelon (Cucumis melo L.) ripening [28]. Another key gene, OsSPL14, was found to increase rice yields and enhance lodging resistance by controlling the number of tillers and increasing the mechanical strength of the stalks, and it has been successfully applied to breed improvement of Indica cultivars [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Thousand grain weight was determined by measuring the weight of harvested seeds that were air-dried in a glasshouse and ovendried at 50°C until they reached~14.0% moisture content. Panicle-related traits containing panicle length, primary branches number, secondary branches number and grain number per panicle were measured from main tillers of 15 plants in WT and transgenic lines respectively (Kim et al, 2018). All data are analyzed by the LSD-test.…”
Section: Phenotype Measurement Of Agronomic Traitsmentioning
confidence: 99%
“…() quantified 49 panicle phenotypes in 242 tropical rice accessions with the imaging platform PANorama and identified 10 candidate genes in pathways known to regulate plant architecture. Recently, it has been demonstrated that through marker‐assisted selection (MAS) OsSPL14 WFP allele dramatically increased grain yield/panicle by 10.6–59.3% in four different genetic backgrounds (Kim et al ., ). Similarly, genome editing approach was used to alter two yield attributing genes namely, Gn1a and DEP1 .…”
Section: Introductionmentioning
confidence: 97%